Odpowiedzi

2010-02-16T19:04:33+01:00
A)4c-(3c+2)-10c=
=4c-3c-3-10c=
=-9c-2
b).9y-(8-3y)+16=
=9y-8+3y+16=
=12y=8
c)-(-5c-8)+6-9c-c=
=5c+8+6-10c=
=-5c+14
e)7x-8-(5x+6)=
=7x-8-5x-6=
=2x-14
f).5x-(2-4x)+8x-7=
=5x-2+4x+8x-7=
=-9+17x
g).5(3z-7)-9(-8z-6)=
=15z-35+72z+54=
=87z+19
h)-3(5x-4)+8(-3x+2)=
=-15x+12-24x+16
=-39x+28
i)7x-3(5x+2)-6(7+2x)=
=7x-15x-6-42-12x=
=-20x-48
j)-5(3y-7)-2(6+4y)+3y=
=-15y+35-12-8y+3y=
=-20y+23
k)-4(3x-6)-3(2+7x)=
-12x+24-6-21x=
=-33x+18
2010-02-16T22:01:32+01:00
A.4c-(3c+2)-10c= 4c-3c-2-10c = -9c-2
b.9y-(8-3y)+16= 9y-8+3y = 12y-8
c.-(-5c-8)+6-9c-c= 5c+8+6-9c-c = -5c+14
e.7x-8-(5x+6)= 7x-8-5x-6 = 2x-14
f.5x-(2-4x)+8x-7= 5x-2+4x+8x-7 = 17x-9
g.5(3z-7)-9(-8z-6)= 15z-35+72z+54 = 87z+19
h.-3(5x-4)+8(-3x+2)= -15x+12-24x+16 = -39x+28
i.7x-3(5x+2)-6(7+2x)= 7x-15x-6-42-12x = -20x-48
j.-5(3y-7)-2(6+4y)+3y= -15y+35-12-8y+3y = -20y+23
k.-4(3x-6)-3(2+7x)= -12x+24-6-21x = -33x+18